2006
DOI: 10.1007/s00125-006-0535-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute hypoglycaemia on memory acquisition and recall and prospective memory in type 1 diabetes

Abstract: Aims/hypothesis Global memory performance is impaired during acute hypoglycaemia. This study assessed whether moderate hypoglycaemia disrupts learning and recall in isolation, and utilised a novel test of prospective memory which may better reflect the role of memory in daily life than conventional tests. Subjects and methods Thirty-six subjects with type 1 diabetes participated, 20 with normal hypoglycaemia awareness (NHA) and 16 with impaired hypoglycaemia awareness (IHA). Each underwent a hypoglycaemic clam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 40 publications
(44 reference statements)
1
19
0
Order By: Relevance
“…Subjects were blind to clamp order, which was randomized and counterbalanced. Six studies were postponed (two NHA and four IHA) because of symptomatic hypoglycemia or blood glucose Ͻ4.0 mmol/l during the preceding 48 h. Using a modified hyperinsulinemic glucose clamp technique (18), blood glucose was stabilized at 4.5 mmol/l (81 mg/dl) (euglycemia) and maintained for 30 min while subjects practiced the cognitive tests. In the euglycemic condition, glucose was maintained at this level.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were blind to clamp order, which was randomized and counterbalanced. Six studies were postponed (two NHA and four IHA) because of symptomatic hypoglycemia or blood glucose Ͻ4.0 mmol/l during the preceding 48 h. Using a modified hyperinsulinemic glucose clamp technique (18), blood glucose was stabilized at 4.5 mmol/l (81 mg/dl) (euglycemia) and maintained for 30 min while subjects practiced the cognitive tests. In the euglycemic condition, glucose was maintained at this level.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers discovered specific cognitive deficits, including impaired information processing speed and memory (e.g., Gold et al, 2007;McAulay, Deary, Sommerfield, & Frier, 2006;Warren, Zammitt, Deary, & Frier, 2007), while others reported reduced performance particularly in tasks that require higher mental efficiency (e.g., Brands, Bissels, et al, 2007;Watari et al, 2006; for a review, see also Heller & Macdonald, 1996). The presence and severity of cognitive impairments appear to be associated with the duration of illness and glycemic control.…”
mentioning
confidence: 96%
“…Post hoc calculations showed that the study had good power to detect a 'large' effect, according to Cohen's conventions [26]. We previously published a study of hypoglycaemia during learning and recall of verbal and visual material (this was carried out after the present study and could not inform its sample size) [15]. The greatest effect of hypoglycaemia was seen for delayed verbal memory, with a 'medium' effect equivalent to approximately 0.6 standard deviations.…”
Section: Discussionmentioning
confidence: 92%
“…We have recently demonstrated that moderate hypoglycaemia impairs both learning and recall [15]. If hypoglycaemia also impairs consolidation, then depending on the duration of the consolidation process, it could impair recall of information learned prior to the onset of hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%